Spatial changes management in order to ensure economic security - O. В. Kozhevina (Управление)
The issues of spatial changes in the context of measures to ensure the economic security of territories (regions, municipalities) have been considered. The key factors of spatial polarization, regional and intraregional socio-economic differentiation in the Russian Federation have been noted. The causes of sparseness and fragmentation of the economic space of the Russian Federation have been revealed. As shown by the study, the theory of spatial changes is only being formed as a separate direction of the spatial economy. A review of foreign and domestic literature in the field of spatial changes made it possible to identify their main characteristics, in particular, orientation towards sustainable development, transformation of cities and the formation of agglomerations, the development of the urban environment, spatial compression and expansion of territories, the formation of innovative opportunities for spatial changes.A comparative analysis of the traditional and growth-oriented entrepreneurial policy allowed us to reveal the differences, disadvantages and advantages of the transition to a model of entrepreneurial economy in the regions. The comparison was carried out according to such parameters as: the key task, emphasis, the goal of entrepreneurial policy, forms of support, sources of financing, protection of intellectual property and personalization of business, institutional measures.The expediency of applying the approaches of spatial changes and spatial innovation-entrepreneurial ecosystems to increase the competitiveness of territories and ensure economic security at the level of the constituent entities of the Russian Federation has been empirically substantiated. The peculiarity of the innovation-entrepreneurial ecosystems approach is that it emphasizes the context of productive (resultant) entrepreneurship.In conclusion, conclusions have been formulated, in particular, about the need for phased spatial changes (design and transformation stages), taking into account the peculiarities of the implementation of the spatial transformation mechanism at each stage.